Proximinality in generalized direct sums - Darapaneni Narayana; T. S. S. R. K. Rao (International Journal of Mathematics and Mathematical Sciences)
We consider proximinality and transitivity of proximinality for subspaces of finite codimension in generalized direct sums of Banach spaces. We give several examples of Banach spaces where proximinality is transitive among subspaces of finite codimension.